How ambidextrous entrepreneurial leaders react to the artificial intelligence boom - Indravathy, Kandasamy; Abd Rahim, Noorlizawati (IAES International Journal of Artificial Intelligence (IJ-AI), 2025)
Artificial intelligence (AI) now plays a central role in enhancing business competitiveness by transforming systems, frameworks, and managerial strategies. This study employs a systematic literature review (SLR) approach, utilizing the 'Consensus AI' search platform to explore the characteristics and roles of ambidextrous entrepreneurial leaders in the AI era. Consensus AI is an AI-powered search engine that automates the processes of reviews, literature searches, screening, and data extraction. It also utilizes 'research question searches' within SLRs to avoid the challenges of ambiguity and irrelevant information associated with 'keyword searches,' delivering more directly relevant results and finding featured snippets that answer specific questions. A research gap exists concerning how ambidextrous leadership adapts to the AI boom, highlighting leadership dynamics in the digital age. The findings emphasize the critical role of ambidextrous entrepreneurial leadership (AEL) in guiding organizations through the AI boom, enabling them to leverage AI for innovation, agility, and competitiveness. Organizations that effectively implement AEL by integrating AI technologies can position themselves for long-term success. Key insights show the importance of AEL approaches, and future research may explore challenges that arise for ambidextrous entrepreneurial leaders in the era of AI, such as ethical considerations and organizational culture.